2018
DOI: 10.3390/w10060680
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Characteristics of Spur Dike Scour under Clear-Water Scour Conditions

Abstract: Factors such as flow and sediment characteristics affecting the spur dike's local depth of erosion have yielded considerable research results, but there is little discussion of the geometry of the spur dike's local scour holes. This study focuses on the spatial characteristics of the geometry of local scour holes in straight-wall spur dikes. The discussion shows that the spur dike arrangement clearly changes the plane geometry of the scour hole. The maximum scour depth has a power function relationship with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The flow depth and velocity at the upstream of the spur dike are all constant, at h = 0.15 m; U = 0.21 m/s, respectively. The flow intensity U/U c = 0.87, U c is the incipient velocity of sediment [13], which belongs to Clear-Water scour conditions. Before the experiment, the bed of the experimental area is kept flat, and the water was slowly stored in the flume to the design depth, adjusting the speed of the axial flow pump, reaching the design flow strength, and carrying out the scour experiment.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The flow depth and velocity at the upstream of the spur dike are all constant, at h = 0.15 m; U = 0.21 m/s, respectively. The flow intensity U/U c = 0.87, U c is the incipient velocity of sediment [13], which belongs to Clear-Water scour conditions. Before the experiment, the bed of the experimental area is kept flat, and the water was slowly stored in the flume to the design depth, adjusting the speed of the axial flow pump, reaching the design flow strength, and carrying out the scour experiment.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…With the passing of time, the profile morphology of the scour hole remains constant. Zhang et al [13] further reported the slope distribution characteristics of the scour hole profile in the spur dike, and thought that its distribution characteristics were closely related to local flow. Although the above literature [6,12,13] has paid attention to the morphological characteristics of scour hole profiles from the time dimension or the spatial dimension, the relevant discussion on profile area of the scour hole with time evolution has not been mentioned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A three-dimensional (3D) view of the spur dike array can be seen in Figure 6. The weight of each block is 155.16 t, and the volume of each block is 64.65 m 3 . The weight of the core stone ranges from 1 kg to 100 kg, and the thickness of the core stone layer is 3 m. The weight of the armor stone ranges from 200 kg to 300 kg, and the armor stone layer is 4 m high.…”
Section: The New Type Of River Training Structure On the Yangtze Rivermentioning
confidence: 99%
“…At present, research on channel training structures is mostly focused on the damage mechanism, such as local scour in the vicinity of the structures [1][2][3] and turbulent flow around the structures [4][5][6], and how changes in structure design parameters affect the water flow and sediment transport characteristics [7,8]. Little research about evaluating the damage level of the channel training structures has been carried out so far.…”
Section: Introductionmentioning
confidence: 99%